How Can The Information System Be Successful In Its Implementation ? - Anggadini, Sri Dewi (Archives of Business Research, 2018)
This research was conducted at the Large Pharmacy Company (PBF) in Bandung Indonesia. The phenomenon is there is the heterogeneity of procedures and deviations process which occur due to non-integrated information systems. The method used in this research is descriptive method that is used to describe each of the studied variables. Verification with path analysis is used to determine the influence of user’s ethics and user’s competence on the quality of AIS and its effect on the quality of accounting information. The results showed that user’s ethics and user’s competence have significant influences on the quality of AIS, and the quality of information systems has implications on the quality of accounting information.